Work productivity and activity impairment in patients with chronic rhinosinusitis undergoing endoscopic sinus surgery—A prospective, multi‐institutional study. Issue 3 (23rd August 2022) - Pandrangi, Vivek C.; Mace, Jess C.; Kim, Jee‐Hong; Geltzeiler, Mathew; Detwiller, Kara Y.; Soler, Zachary M.; Schlosser, Rodney J.; Alt, Jeremiah A.; Ramakrishnan, Vijay R.; Mattos, Jose L.; Smith, Timothy L.
Abstract: Background: Productivity loss and activity limitations due to chronic rhinosinusitis (CRS) are known to contribute to the significant economic and personal burden of disease. The purpose of this study was to assess productivity and activity impairment before and after endoscopic sinus surgery (ESS) for medically refractory CRS. Methods: This investigation was a prospective, multi‐institutional, observational cohort study. Patients diagnosed with medically refractory CRS completed the Work Productivity and Activity Impairment—Specific Health Problem (WPAI‐SHP) questionnaire before surgery and approximately 6 months after the procedure. Factors associated with minimal clinical important differences (MCIDs) for productivity and activity impairment were identified. Results: A total of 279 study participants were screened for inclusion, of whom 176 (63.1%) with postoperative follow‐up were included in the final cohort. Preoperative productivity and activity impairment were observed in 63.2% and 69.8% of the patients, respectively. Among these patients, postoperative improvement equaling at least 1 MCID was reported in both productivity (76.1%) and activity (76.4%) impairments. Multivariate regression identified sphenoidotomy (odds ratio [OR], 4.18; 95% confidence interval [CI], 1.03‐17.02) as the only factor associated with increased likelihood of productivity improvement, whereas septoplasty during ESS (OR, 8.45; 95% CI, 2.33‐30.68) and migraine (OR, 0.35; 95% CI, 0.12‐0.96) were associated with differential odds of activity improvement. Conclusion: CRS is associated with a substantial burden on productivity and activity that significantly improves after treatment with ESS. These data may facilitate improved patient counseling and shared decision‐making regarding surgical management for CRS.